2004
DOI: 10.1177/095440540421800501
|View full text |Cite
|
Sign up to set email alerts
|

Laser shock processing of Ti-6Al-4V alloy

Abstract: Laser shock processing of Ti-6Al-4V alloy is considered. A mathematical model governing the laser non-conduction-limited heating is introduced and a numerical solution for the temperature distribution is presented. The pressure (recoil pressure) generated across the solid-vapour interface is determined and it is considered as an impact load for the elastic-plastic wave generation in the surface region of the substrate material. The depth of the plastic region is predicted from the elastic-plastic wave propagat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…However, it was reported that the difference between the maximum for one and two shocks was 30 [53]. Therefore, it can be seen from Figure 14 and the ΔHV data from [53] that the difference between the minimum and maximum values are relatively close as compared to the ΔHV data from [93]. The variations observed by Yilbas et al [93] and Zhang et al [53] could be due to the initial conditions of the treated sample or processing parameters.…”
Section: Effect Of Laser Shock Peeningmentioning
confidence: 79%
See 3 more Smart Citations
“…However, it was reported that the difference between the maximum for one and two shocks was 30 [53]. Therefore, it can be seen from Figure 14 and the ΔHV data from [53] that the difference between the minimum and maximum values are relatively close as compared to the ΔHV data from [93]. The variations observed by Yilbas et al [93] and Zhang et al [53] could be due to the initial conditions of the treated sample or processing parameters.…”
Section: Effect Of Laser Shock Peeningmentioning
confidence: 79%
“…From this figure, it is evident that moving away from the shocked region results in hardness decrease to the base material, which has been attributed to the presence of tensile stresses [82]. Yilbas et al [93] also found that the microhardness of the Ti-6Al-4V after LSP was 1.5 times of the base material as shown in Figure 15. The hardness increase was attributed to the increased dislocation densities [49,76,85,128] and twinning deformation [82,96].…”
Section: Effect Of Laser Shock Peeningmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the examples of the surface modification techniques is the laser shock processing. Laser shock processing (LSP) is an innovative surface treatment, with which mostly a Q-switched Nd:YAG laser with short pulses of several nanoseconds and with a power density, in the pulse peak, of as much as several tens of GW/cm 2 is used [ 1 , 2 ]. The high magnitude stress wave generated by the interaction between the high-power, short pulsed lasers and the materials can produce plastic deformation.…”
Section: Introductionmentioning
confidence: 99%